Development of graphical user interface (GUI) in application of productivity rate for rotor arrangement with parallel action automated flow line - Wong, Yok Shiuan (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
In the application in industry, productivity rate can be calculated with the mathematical model of the automated flow line. Automated flow lines are universal and widely used in industry which can be either in a linear arrangment or ortor arrangement. complicated of manual calulaction methematical model result in higher failure rate and time consume. A computational system is required, which can be applied to meansure, predict, analysis and improve the productivity